Autopoietic interaction systems: micro-dynamics of participation and its limits. Issue 4 (1st October 2020) - Chettiparamb, Angelique
ABSTRACT: This article engages with two published case studies describing participation in planning, a much-discussed aspect of spatial planning. After a brief review of the arguments advanced in the articles, the case studies are reinterpreted using the theory of social autopoiesis as advanced by Niklas Luhmann, in particular, one concept from the theory – interaction systems. The re-analysis yields two results: it illustrates the added contribution that the theory can make to understand public participation in spatial planning, but also highlights particular issues in relation to participatory planning and its use in spatial planning.